Tadzhikistan-Russia: Geopolitical Relations at the Turn of the Century - Z. S. Saidzoda (Vestnik MGIMO-Universiteta)
RETRACTEDIn this article the writer analyses the development peculiarities of the Tajik-Russian geopolitical relations during the establishment of Tajikistan foreign policy up to the commencement of multi-vector «open doors» policy in 2003-2004. Since the establishment of peace and stability in Tajikistan beginning from the year of 2000 the socio-economic development issues have been set as prior actions. To boost the economy, attraction of foreign investments, creation of new jobs and improvement of life standard of population were the issues to address. Political leaders of Tajikistan had no right to waste time making no headway. The country inevitably faced the issue of diversification of interstate and foreign economic relations, including outside the CIS. The article highlights that the foreign «open door» policy declared at the turn of2002-2003 implied mandatory modernization of the Tajik-Russian cooperation through strengthening its economic and human dimensions, adjusting the strategic partnership and alliance between the two states to the new global political realities. As to the geopolitical and military-political priorities, which Tajikistan had firmly adhered throughout the entire 1990th since its Independence, they actually remained unchanged even after 2002. The author points out the long-term Russian presence in the form of a large scale military base and military infrastructure on the territory of Tajikistan. The Republic is one of the most consistent, active and disciplined members of the Collective Security Treaty Organization. During the first decade of the XXI century the political leaders of Tajikistan had been receiving offers from foreign non CIS countries with regard to deployment of military facilities on a fee basis on the territory of Tajikistan which were not even considered by the Government. Thus, the multi-vector foreign policy of «open doors» has been reflected in diversification of the international relations of Tajikistan, in demonopolization of trade and economic priorities, in attraction of foreign investments and military-technical assistance from the third countries (other than CIS and CSTO countries) but completely preserving the geopolitical and military-political priorities established until 2002.